Detection of colorectal‐cancer‐associated bacterial taxa in fecal samples using next‐generation sequencing and 19 newly established qPCR assays - Thulasika Senthakumaran; Tone M. Tannæs; Aina E. F. Moen; Stephan A. Brackmann; David Jahanlu; Trine B. Rounge; Vahid Bemanian; Hege S. Tunsjø (Molecular Oncology)
We have previously identified increased levels of distinct bacterial taxa within mucosal biopsies from colorectal cancer (CRC) patients. Following prior research, the aim of this study was to investigate the detection of the same CRC‐associated bacteria in fecal samples and to evaluate the suitability of fecal samples as a non‐invasive material for the detection of CRC‐associated bacteria. Next‐generation sequencing (NGS) of the 16S ribosomal RNA (rRNA) V4 region was performed to evaluate the detection of the CRC‐associated bacteria in the fecal microbiota of cancer patients, patients with adenomatous polyp and healthy controls. Furthermore, 19 novel species‐specific quantitative PCR (qPCR) assays were established to detect the CRC‐associated bacteria. Approximately, 75% of the bacterial taxa identified in biopsies were reflected in fecal samples. NGS failed to detect low‐abundance CRC‐associated taxa in fecal samples, whereas qPCR exhibited high sensitivity and specificity in identifying all targeted taxa. Comparison of fecal microbial composition between the different patient groups showed enrichment of Fusobacterium nucleatum, Parvimonas micra, and Gemella morbillorum in cancer patients. Our findings suggest that low‐abundance mucosa‐associated bacteria can be detected in fecal samples using sensitive qPCR assays.